Reverdin-Isham modified vs MICA for moderate hallux valgus: A comparative study - Ribeiro Xavier, Nivea; Ribeiro Lara, Luiz Carlos; Pinheiro de Lima, Frederico; Tondato da Silva Costa, Letícia; Furtado Lancia, Lara; Bordignon, Glaucia; Abrahão Rosa Vaz, Gabriela (Journal of the Foot & Ankle, 2026)
Introduction: Minimally invasive surgery has emerged as a promising alternative in the treatment of hallux valgus (HV); however, the literature lacks direct comparisons between percutaneous techniques. The purpose of this study is to compare the clinical, functional, and radiographic outcomes of the Modified Reverdin-Isham (RImod) and minimally invasive Chevron-Akin (MICA) techniques in the treatment of moderate VH. Methods: Retrospective comparative study of 81 feet (38 MICA, 43 RImod) with moderate hallux valgus (IMA ≤ 18°, HVA ≤ 40°). Preand postoperative evaluations (6 months) included the AOFAS score, intermetatarsal angles (IMA) and hallux valgus angle (HVA), and fibular sesamoid subluxation. Statistical analysis used Student’s t-test and Wilcoxon’s t-test, with adjustment for bilateral testing. Results: Both groups demonstrated significant improvement (p < 0.001) in AOFAS (MICA: 37.9 ± 12.6 → 90.95 ± 8.1; RImod: 40.47 ± 13.1 → 93.4 ± 6.5), IMA (MICA: 14.9 ± 2.1° → 10.0 ± 3.0°; RImod: 14.4 ± 2.1° → 10.0 ± 2.8°), HVA (MICA: 31.3 ± 6.1° → 11.8 ± 5.7°; RImod: 29.0 ± 5.8° → 11.0 ± 4.4°) and fibular sesamoid recentralization (MICA: 89% → 53%; RImod: 82% → 51 %). There was no statistically significant difference between the techniques for functional gain (p = 0.98), IMA correction (p = 0.43), HVA (p = 0.30), or sesamoid recentralization (p = 0.41). The complication rate was 21.1% for MICA and 9.3% for RImod (p = 0.149), with a distinct profile: MICA was associated with implant complications and recurrence, while RImod was associated with nerve injury and malunion. Conclusion: RImod and MICA are effective for the correction of moderate hallux valgus, with comparable clinical and radiographic results. MICA allows greater angular correction of the IMA but carries a risk of complications related to the synthesis material; RImod eliminates this risk and has a lower complication rate. The surgical decision must be individualized.